2017
DOI: 10.1038/bmt.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

Use of haploidentical stem cell transplantation continues to increase: the 2015 European Society for Blood and Marrow Transplant activity survey report

Abstract: Hematopoietic stem cell transplantation (HSCT) is an established procedure for many acquired and congenital disorders of the hematopoietic system. A record number of 42 171 HSCT in 37 626 patients (16 030 allogeneic (43%), 21 596 autologous (57%)) were reported by 655 centers in 48 countries in 2015. Trends include continued growth in transplant activity over the last decade, with the highest percentage increase seen in middle-income countries but the highest absolute growth in the very-high-income countries i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
224
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(234 citation statements)
references
References 18 publications
1
224
0
9
Order By: Relevance
“…Consequently, haplo-HCT is increasingly used in Europe while the use of CBT is declining (36). Several recent studies assessing the impact of donor type on transplantation outcomes have been reported (19,24,(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, haplo-HCT is increasingly used in Europe while the use of CBT is declining (36). Several recent studies assessing the impact of donor type on transplantation outcomes have been reported (19,24,(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…All P values are 2 side the analyses were performed using the statistical software SAS version 9.4 ( Sixty-five HSCT centers from 25 countries reported data on 655 GNR episod 591 patients (1.1 episodes [range, [1][2][3][4] Abbreviations: allo, allogeneic; auto, autologous; βL/βLI, β-lactam/β-lactamase inhibitor; GVHD, g host disease; HSCT, hematopoietic stem cell transplant; ICU, intensive care unit.…”
Section: Microbiological Workupmentioning
confidence: 99%
“…In recent years, the share of HPC transplants that used haploidentical sources has been rising (see Text Box 3 in Chapter Four), while the share of CBU transplants has fallen, both in the United States and abroad. 151 In this section, we explore the potential for further growth in the relative number of haploidentical HSC transplants, which might contribute to lower demand for cord blood and increasing financial pressure on CBBs. Investments in infrastructure and training that support haploidentical transplants and reduced investments in cord blood infrastructure and training may be self-perpetuating.…”
mentioning
confidence: 99%